THE ART OF EXCELLENT STUDY IN THE CREATIVE CREATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, some aspects of Muqimi's skills as an artistic poet are shown, how skillfully he uses husni talil, which is one of the delicate and complex arts of Eastern poetics.